Currículo intercultural: a arte como sistema simbólico cultural na escola de branco: um estudo a partir da arte na educação escolar, na aldeia tupi-guarani de Piaçaguera - Sánchez, Janina Moquillaza (2006)
This is a qualitative ethnographic research, approached through the action-research method. From the problem of limitations to access the human right to quality education, I intended to know the ways to enhance self esteem of indigenous teachers through the means of art, by accessing theoretical discourses and appropriating of knowledges in intercultural relations. Specifically, I observed the case of a group of the Tupi-guarani linguistic branch in the State of São Paulo. For the paradigmatic orientation of this thesis I adopted the cultural anthropological theory of Clifford Geertz, to whom it is a net of meanings invented by man. Within the net of relations between the whites culture of education and indigenous culture of education, I developed a theoretical comprehension of culture as empowered mechanisms, controls, instructions to govern behavior, and adopting Geertz idea of art as a cultural symbolic system, I found a cultural collective production as the materialization of a way of living. Also, I based on Vygotsky s thoughts about the psychology of art, aesthetics on education, on current life and on behavior, the use of language, the social formation of mind and the importance of mediation. I researched about socio-historical circumstances of indigenous intercultural education as the action-research was developed at the Piaçaguera Tupi-guarani village, in Peruíbe, interior of São Paulo. As the problem configurated, and wiling to reveal the truth of the hypothesis of teachers low self-esteem, we developed a process of life history researches in the same village, sharing knowledges and stimulating the use of abilities to create, recovering ancient knowledges, and recognizing of possibilities of the use of artistic languages, in indigenous education. I consider that intercultural education is a challenge to contemporary education and that in the differentiated indigenous education persist ideas of the school of whites. I found important ways of how this is affecting and will affect indigenous populations, remaining some questions such as how this people use and will use their strength to also affect it; answer that will surely be given by us and by future generations. Concluding, I found that it was possible to contribute to enhance the self esteem of the indigenous group, to recover some elements of the cultural symbolic system, to promote art in education and in the life of people of the indigenous Piaçaguera village